Satisfacción de la atención de enfermería en usuarios del Centro de Salud Anidado Vilcabamba del Cantón Loja - Cabrera Reyes, Estefania Alejandra (2023)
Satisfaction is the measurement of user’s expectations when regarding to sanitary care and health, and it is highly important in the everyday life as it embraces principles, methods and strategies focused on reaching a better level. The objective of this research was to stablish the satisfaction level among the users of the nursing service in the Anidado Vilcabamba health center in the Loja city for the period 2022. The investigation is a descriptive, quantitative, prospective and crosssectional study, the sample included a population of 67 users who come to the health center and who meet the inclusion and exclusion criteria. All of them accepted to sign the written informed consent. Data collection: for gathering the information, the Caring Assessment Instrument (CAREQ) created by Patricia Larson was applied. It consists of 46 items that evaluate the nursing performance in term of accessibility, accurate explanations, facilitation, comfort, anticipations, a trust based relationship, monitoring and follows up of patients. The results obtained were that of the 67 users who participated in the research, 68.7% are female and 31.3% male, the most frequent age range was 20-64 years with 83.6% of the total sample. 44% of the users showed a medium level of satisfaction, 25.04% expressed low satisfaction and other users (29.9%), showed a high level of fulfilment. Most of the users surveyed who took part in the study showed a medium level of satisfaction in terms of the care provided by the nursing staff at Anidado Vilcabamba health center.